The Rare Earth Elements: An in-Depth Exploration of Industrial Utilization, Recycling Potential and Environmental Ramifications - Owolabi, Joseph; Kizito, Emeje (Engineering And Technology Journal, 2024)
This comprehensive study delves into the extensive spectrum of applications attributed to rare earth elements (REEs), their potential for effective recycling, and the intricate environmental considerations entwined with their extraction and utilization. The realm of rare earth elements is undergoing rapid transformations fueled by technological progress and the escalating demand for these essential components. The spectrum of REEs encompasses the lanthanide series elements, namely La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, as well as Sc and Y. These metals currently hold utmost significance across a multitude of contemporary technologies, spanning from smartphones, televisions, LED light bulbs, to wind turbines. This paper concisely outlines the environmental perils encompassing human health that stem from REE mining practices and the large-scale disposal of electronic waste containing noteworthy concentrations of REEs. Within these pages, we encapsulate novel strategies aimed at ensuring the future availability of REEs, including recent advancements in REE extraction from Coal Field Ash and innovative e-waste recycling methodologies. Additionally, we spotlight recent breakthroughs in the domain of individual REE separation techniques, encompassing both metallurgical and recycling operations.